1985
DOI: 10.1063/1.336152
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of charge trapping in dielectrics

Abstract: Transient electronic conduction in thermally grown SiO2 has been shown to be limited by space-charge evolution. The space charge originates from trapping of the injected species. It induces a field which affects the emission of charges at the injecting electrode. The trapping of charge has been analyzed on the basis of three, essentially different, mechanisms: (1) first order trapping, (2) first order trapping which takes into account that trapped charges repel injected charges, and (3) trapping which increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(42 citation statements)
references
References 15 publications
3
39
0
Order By: Relevance
“…We have no indication that the failure of the constant-Q bd model for our junction breakdown could be related to the occurrence of a current density exceeding a certain critical value, J cr , above which the density of occupied trap states is very high. In such a case the conductivity would be observed to change an order of magnitude with time in a constant applied voltage experiment, 18 a phenomenon that we did not observe.…”
Section: A Q Bd Modelmentioning
confidence: 71%
See 3 more Smart Citations
“…We have no indication that the failure of the constant-Q bd model for our junction breakdown could be related to the occurrence of a current density exceeding a certain critical value, J cr , above which the density of occupied trap states is very high. In such a case the conductivity would be observed to change an order of magnitude with time in a constant applied voltage experiment, 18 a phenomenon that we did not observe.…”
Section: A Q Bd Modelmentioning
confidence: 71%
“…For the case of tunneling across SiO 2 strong experimental support in favor of the wearing mechanism has been obtained by Wolters and van der Schoot, 18 who observed that for 8-40 nm SiO 2 -based capacitors under certain conditions the breakdown probability density depends on the total amount of tunneled electrons, the ͑electron͒ charge to breakdown, Q bd , which is the electron current density integrated until breakdown. The quantity Q bd ͑averaged over a large ensemble͒ was found to be independent of the type of experiment employed ͑e.g., constant voltage or current, or ramped voltage or current͒.…”
Section: A Q Bd Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that some defects can trap both electron and hole although the trap may have different energy levels for each type of charge carrier. 8 There have been a series of attempts to understand trapping behavior over the years as the formation of space charge in solid dielectrics has been considered as a key component to understand ageing phenomenon in the insulating materials.…”
Section: B Trapping Processmentioning
confidence: 99%